From Corruption to Declining Public Trust: Implications for Political Participation in West Aceh Regency - Najamudin; Sudarman; Fadhly, Zuhrizal; Asmaul Husna, Cut; Wahyu Handayani, Sri (Universitas Brawijaya, 2026)
Corruption is a major challenge in democratic governance because it has a broad impact on societal conditions, particularly economic conditions. For example, political participation shapes public trust in West Aceh Regency. This study uses a qualitative case study approach. Interviews with 10 informants and relevant documents will be conducted. This activity shows that citizens view corruption as a lack of accountability and transparency, and as the unethical use of public resources, not just as a violation of the law. This indicates a decline in public trust in local government institutions, both electoral and non-electoral, due to corruption. This study also examines the impact of corruption on the character of citizen engagement and the weakening of institutional legitimacy, which in turn affects the relationship between society and the state. The results of this study are important for improving formal accountability, transparency, and public oversight mechanisms to encourage more meaningful political participation and rebuild trust in local government bodies. This research is expected to deepen understanding of how citizens perceive corrupt behavior and its influence on local political affairs.